2018
DOI: 10.18203/2349-2902.isj20180112
|View full text |Cite
|
Sign up to set email alerts
|

Age distribution pattern of female breast cancer patients in Bangladesh- developing early and presenting late

Abstract: Background: Carcinoma of the breast is the most common malignancy in females. At present carcinoma breast is the leading cancer in Bangladesh and is competing cancer cervix in incidence. Epidemiological studies at regional and global levels suggest the occurrence of carcinoma breast at a younger, premenopausal age in Indian and Asian women as compared with western women. Knowledge of this factor emphasizes the need to modify the timing of modalities of detection of early carcinoma and its management. According… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 6 publications
1
3
0
Order By: Relevance
“…Most of the patients in the study was in between 50-60 years and least patient was in age between 30-40 years and 70-80 years which was consistent with study conducted by Neesa et al (2018). They showed the similar findings, age range of their study subject was 32 to 81 years and least patient was in age group <40 years and >80 years (4). Another study conducted by Lee et al (2011) also found the similar results (5).…”
Section: Discussionsupporting
confidence: 66%
“…Most of the patients in the study was in between 50-60 years and least patient was in age between 30-40 years and 70-80 years which was consistent with study conducted by Neesa et al (2018). They showed the similar findings, age range of their study subject was 32 to 81 years and least patient was in age group <40 years and >80 years (4). Another study conducted by Lee et al (2011) also found the similar results (5).…”
Section: Discussionsupporting
confidence: 66%
“…This result finding was in the same line with (Salehi et al, 2017) [36] who mentioned that the mean age at the time of diagnosis www.nursingjournal.net was 48.8 ±12.01. Also, (Nessa et al, 2018) [33] reported that the highest percentage of studied women was above 40 years. This finding may be justified that aging process is one of the most important risk factors of breast cancer because of the longer life expectancy, changes in reproductive patterns in women over 40 years, menopausal hormonal use, rising prevalence of obesity, and genetic damage (mutations) in the body at this age.…”
Section: Discussionmentioning
confidence: 94%
“…Its incidence in Pakistan is 2.5 times higher than that in neighboring countries like Iran and India [1]. The risk factors associated with breast cancer are age, family history, early menarche, nicotine consumption, 1 st child birth, physical inactivity and lack of awareness regarding the disease [8].…”
Section: Discussionmentioning
confidence: 99%